Ferritin level may be a major factor in young females with recurrent aphthous stomatitis - Dar-Odeh, Najla; Abu-Hamamd, Osama (Journal of Contemporary Medical Sciences, 2019)
Recurrent aphthous stomatitis is considered the most common type of recurrent oral ulcers that affects adversely the quality of life of patients. Its etiology is not well understood, however, nutritional and psychosocial factors have been suggested in a certain category of patients. The aim of this case series is to describe the hematological picture namely hemoglobin level, serum vitamin B12 and serum ferritin in six young female patients affected by recurrent aphthous stomatitis, and to report its association of low serum ferritin.